Effect of curcumin on leukocyte-endothelium interaction in rats with nonsteroidal anti-inflammatory drugs induced peptic ulcer - Sakonwan Chuchuai (Chulalongkorn University, 2012)
Thesis (M.Sc.)--Chulalongkorn University, 2009